Enzymatic resolution of 3-butene-1,2-diol in organic solvents and optimization of reaction conditions - F. Secundo; M. L. Oppizzi; G. Carrea; M. De Amici; C. Dallanoce (Biocatalysis and Biotransformation, 1999)
Lipases from different sources were tested in the kinetic resolution of 2-hydroxy-3-butenyl butanoate {[(R,S)-2] carried out by transesterification of the secondary alcohol. The influence of organic solvent. acyl donor and temperature on the enantioselectivity and activity of lipases was also investigated. Our study showed that both R-(+)-2 and S-(-)-2 could be obtained in high enantiomeric purity (ee greater than or equal to 99%) and satisfactory yield (29% and 27%, respectively). Among the enzymes tested, lipase from Candida antarctica B (CALB) showed the highest preference for the (R)-enantiomer (E = 26 at -13 degrees C), whereas lipase from Pseudomonas fluorescens (lipase AK) acylated the (S)-enantiomer preferentially (E = 18 at -9 degrees C).}